A Prospective Observational Study on Profile of Neurological Emergencies in an Emergency Department of a Tertiary Care Teaching Hospital - Ganesan, Rajanandh Muhasaparur (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2021)
Background: Emergency departments are the typical initial contact for seriously ill and injured patients. Although diverse and sometimes subtle in presentation, acute neurological diseases have an urgency that makes their rapid diagnosis and treatment crucial for improving outcomes. Methodology: A prospective observational study was conducted during October 2020–January 2021 at the Emergency Department of Sri Ramachandra Medical Centre. Results: A total of 155 emergency cases were evaluated in the department during this period. The ages of the patients ranged from 18 to 97 years with a mean age of 49.76 years and the median age of 50 years. There were 104 males and 51 females. Stroke was the most frequent neurologic emergency and was identified in 137 (89%) patients, with 97 (70.8%) of these patients being male while 40 (29.2%) were females. Conclusion: The total percentage of the stroke patients that were under 50 years of age was 33 (21%), while those over 50 constituted 104 (78%). The second most common diagnosis was seizure found in 10 patients (6%).